Effect of daily fraction size on laryngoesophageal dysfunction after chemoradiation for squamous cell carcinomas of the larynx and hypopharynx. Issue 7 (16th March 2017) - Chen, Allen M.; Hsu, Sophia; Meshman, Jessica; Chin, Robert; Beron, Philip; Abemayor, Elliot; St. John, Maie
ABSTRACT: Background: The purpose of this study was to determine the effect of fraction size on laryngoesophageal dysfunction among patients treated by chemoradiotherapy for laryngeal and hypopharyngeal cancer. Methods: Forty patients underwent chemoradiotherapy for stage III/IV squamous cell carcinomas of the larynx and hypopharynx. Median radiation dose was 70 Gy (range, 69.3–70.4 Gy) with daily fractionation ranging from 2 Gy to 2.2 Gy. Results: When comparing 2 Gy versus >2 Gy daily fractionation, there was no difference in 2‐year overall survival (71% vs 72%; p = .68), locoregional control (79% vs 77%; p = .43), or laryngectomy‐free survival (60% vs 61%; p = .72). Use of 2 Gy versus >2 Gy fractionation improved laryngoesophageal dysfunction‐free survival (2‐year estimates, 49% vs 27%; p = .07). Patient‐reported voice and swallowing were improved with the former. Conclusion: As the importance of a functional larynx becomes recognized as an endpoint for patients treated by voice preservation, the results of our study help refine treatment guidelines. © 2017 Wiley Periodicals, Inc. Head Neck 39 : 1322–1326, 2017